Penulisan Teks Artikel Ilmiah - Risky Sakti Lumban Gaol; Daniel David Sidebang; Taslima Amelia Taufiq (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
The word article is a written work that discusses an issue in such a way that it becomes the main topic. In general, the purpose of writing articles is to educate, influence, persuade, inform and entertain and publish them both in print and online media. So a scientific article is a piece of writing that contains the thoughts, concepts and thoughts of a person or group of people through field and non-research (conceptual) processes which are put into written form and the mechanisms for making them through a systematic structure, methods and certain rules so that their truth can be tested. Research methods are scientific methods used to obtain data for a specific purpose. In this research, the method used is a qualitative research method with a descriptive type of analysis to obtain and answer the various problems being studied. Researchers use the library study method, this method is a technique for collecting reference data sources by reviewing data from literature, scientific journals, books, scientific articles through digital sources that are related to the problems raised in this research.